A study of global atmospheric budget and distribution of acetone using global atmospheric model STOCHEM-CRI. (July 2015) - Khan, M.A.H.; Cooke, M.C.; Utembe, S.R.; Archibald, A.T.; Maxwell, P.; Morris, W.C.; Xiao, P.; Derwent, R.G.; Jenkin, M.E.; Percival, C.J.; Walsh, R.C.; Young, T.D.S.; et al.
Abstract: The impact of including a more detailed VOC oxidation scheme (CRI v2-R5) with a multi-generational approach for simulating tropospheric acetone is investigated using a 3-D global model, STOCHEM-CRI. The CRI v2-R5 mechanism contains photochemical production of acetone from monoterpenes which account for 64% (46.8 Tg/yr) of the global acetone sources in STOCHEM-CRI. Both photolysis and oxidation by OH in the troposphere contributes equally (42%, each) and dry deposition contributes 16% of the atmospheric sinks of acetone. The tropospheric life-time and the global burden of acetone are found to be 18 days and 3.5 Tg, respectively, these values being close to those reported in the study of Jacob et al. (2002). A dataset of aircraft campaign measurements are used to evaluate the inclusion of acetone formation from monoterpenes in the CRI v2-R5 mechanism used in STOCHEM-CRI. The overall comparison between measurements and models show that the parameterised approach in STOCHEM-NAM (no acetone formation from monoterpenes) underpredicts the mixing ratios of acetone in the atmosphere. However, using a detailed monoterpene oxidation mechanism forming acetone has brought the STOCHEM-CRI into closer agreement with measurements with an improvement in the vertical simulation of acetone. The annual mean surface distribution of acetone simulated by the STOCHEM-CRI shows a peak over forested regions where there are large biogenic emissions and high levels of photochemical activity. Year-long observations of acetone and methanol at the Mace Head research station in Ireland are compared with the simulated acetone and methanol produced by the STOCHEM-CRI and found to produce good overall agreement between model and measurements. The seasonal variation of model and measured acetone levels at Mace Head, California, New Hampshire and Minnesota show peaks in summer and dips in winter, suggesting that photochemical production may have the strongest effect on its seasonal trend. Highlights: Photochemical production from monoterpenes gives 64% to the global acetone sources. The tropospheric life-time of acetone is found to be 18 days. Higher acetone is found over the forested regions throughout the summer. Good agreement between model and measurement data for acetone is found.